IMPLEMENTATION OF THE ONE DATA INDONESIA POLICY IN MINAHASA REGENCY - Raymond Nica Seyun Kumolontang; Laurens L. Bulo (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the dynamics and gaps in the implementation of the One Data Indonesia (SDI) Policy in Minahasa Regency, as well as to identify the determinant factors that influence its implementation. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The determination of informants was carried out by purposive sampling, involving Bapelitbangda, the Communication and Information Service, OPDs as data producers, and BPS as data administrators, with data validity tested through triangulation of sources and methods. The results of the study indicate that the implementation of the SDI policy in Minahasa Regency has not been running optimally as mandated by Presidential Regulation Number 39 of 2019. Its implementation is hampered by structural and operational determinant factors, which are characterized by: (1) the late issuance of the Regent's regulation on One Data Indonesia in Minahasa Regency so that the SDI Forum is less active and only five OPDs have submitted the 2025 data list; (2) a critical HR crisis, where the Statistics Division of the Communication and Information Service was combined with the Cryptography Affairs and was only managed by one ASN without any functional statisticians or computer technicians; (3) deviations in business processes from the Generic Statistical Business Process Model (GSBPM) standards due to the lack of submissions of statistical recommendations to BPS; (4) insufficient funding, and (5) information technology infrastructure that is not yet interoperable.